Identify Students' Conceptual Understanding of Momentum Material - Joy, Elaine; She, Trent; McCrory, Amy (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the Study: This research aims to identify the level of students' conceptual understanding of momentum material. Methodology: The type of research used is quantitative research with the method used in this research being descriptive quantitative. The population of this study was 3 high schools in the United States. Main Finding: Based on the research results, it was found that the level of students' understanding of the momentum material was quite good, where for each sub-material the level of understanding was also quite good . Understanding This will of course have an impact on student learning outcomes. This level of understanding will of course change over time according to the student's circumstances, for this reason the teacher's role is needed in guiding students towards better change. Novelty/Originality of the Study: This research is aimed at finding out the level of understanding of concepts, especially momentum and impulse.